PENGARUH PEMBERIAN DOSIS PUPUK ORGANIK DARI LIMBAH PKS PADA MEDIA TANAM SUBSOIL TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT ( Elaeis guineensis jacq ) DI PRE NURSERY - Ramadhinata, Ikhwan; Sijabat, Octanina Sari; Razali, Razali; Nadhira, Ahmad (LPPM Universitas Katolik Santo Thomas Medan, 2023)
This study aims to determine the effect of organic fertilizer from PKS waste on the growthof oil palm seedlings. Research has been conducted in Kec. Patumbak Kab. Deliserdang,Marindal Village I Pasar V North Sumatra from December 9 2022 to March 2023. With analtitude of 25 meters above sea level (above sea level). And the study design model useda non-factorial Randomized Block Design (RBD) with 16 treatment factors, all treatmentsconsisted of 300 g of subsoil, 300 g of sand and 0.4 g of basic fertilizer (BST according toeach ratio). Treatment of organic fertilizer from PKS waste had a significant effect on theparameters of plant height aged 12 mst, leaf area of 6 mst and plant fresh weight of 12mst, but had no significant effect on the parameters of plant height aged 4 to 10 mst,stem diameter of 4 to with 12 weeks of planting, number of leaves from 4 to 12 weeks,leaf area of 4.8, up to 12 weeks and dry weight of 12 weeks of oil palm.